A Retrospective Analysis of Cyanoacrylate Injection versus Hemoclip Placement for Bleeding Dieulafoy’s Lesion in Duodenum - Yu Jiang; Julong Hu; Ping Li; Wen Jiang; Wenyan Liang; Hongshan Wei (Gastroenterology Research and Practice)
Background. Duodenal Dieulafoy’s lesion (DL) is a rare disease that may lead to lethal hemorrhage in the upper gastrointestinal tract. The best technique for endoscopic intervention still remains unclear. In the present study, we performed a retrospective analysis of cyanoacrylate injection versus hemoclip placement for treating bleeding DLs. Materials and Methods. We retrospectively analyzed eighteen patients from three medical centers between October 2008 and February 2016; six patients received cyanoacrylate injection, while hemoclips were placed in 12 patients during the upper gastrointestinal endoscopy. Results. All patients received first endoscopic examination and/or endotherapy within 12 hours of admission to hospital. No difference was observed in the primary hemostasis rate or the recurrent hemorrhage rate between the cyanoacrylate injection (CI) group and the hemoclip placement (HP) group, except that in one patient from the HP group melena was found three days after the first endotherapy. This patient received cyanoacrylate injection once again. Conclusion. Both cyanoacrylate injection and hemoclip placement are effective in treating duodenal DL, and neither of them causes significant side effects.